2019
DOI: 10.1111/dth.12849
|View full text |Cite
|
Sign up to set email alerts
|

Tetra-arsenic tetra-sulfide ameliorates lupus syndromes by inhibiting IL-17 producing double negative T cells

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease of uncertain etiology that affects multiple tissues and organs. Tetra‐arsenic tetra‐sulfide (As4S4), a traditional Chinese medicine, is effective on acute promyelocytic leukemia with mild side effects. In our previous study, BXSB lupus‐prone mice treated with As4S4 has showed improved monocytosis, decreased serum interleukin (IL)‐6 and suppressed skin, liver and renal lesions with well‐tolerance. In this study, we explored the effect and mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Studies have shown that some herbal components in this recipe exhibit anti-inflammatory and immunoregulatory effects. Oxymatrine, an active constituent of Radix Sophorae Flavescentis, protects the organs and tissues by regulating inflammation, oxidative stress, apoptosis, and fibrosis[ 7 - 9 ]. Shibeshi et al [ 10 ] observed that Achyranthis asperae has a regulating effect on serum lipids and hormones (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that some herbal components in this recipe exhibit anti-inflammatory and immunoregulatory effects. Oxymatrine, an active constituent of Radix Sophorae Flavescentis, protects the organs and tissues by regulating inflammation, oxidative stress, apoptosis, and fibrosis[ 7 - 9 ]. Shibeshi et al [ 10 ] observed that Achyranthis asperae has a regulating effect on serum lipids and hormones (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%